The Adaptation Model Of Care Giver In Treating Family Members With Schizophrenia In Kediri East Java - Byba Melda Suhita; Chatarina Umbul Wahyuni; Hari Basuki Notobroto; Ah Yusuf (Jurnal Ners, 2017)
Introduction: Schizophrenia is a severe mental disorder that is characterized by impaired reality (hallucinations and delusions), inability to communicate, affect unnatural or blunt, cognitive disorders (not capable of abstract thinking) and had difficulty doing daily activities. Normally, the family is most affected by the presence of people with schizophrenia in their families. The purpose of this study was to develop an adaptation model of the caregiver in caring for family members with schizophrenia in Kediri.Methods: This study used cross-sectional design with nature explanatory research. Data were collected using a questionnaire on 135 respondents in nine health centers in the city of Kediri region. The sampling technique used simple random sampling. For data analysis and test, the feasibility used a test model of SEM with AMOS program 19.Results: The results showed self esteem caregiver (-0.25 <0.05), community resources (0.24 <0.05), self-efficacy (0.22> 0.05) , caregiver coping effort (12:17 <0.05), and the perception of caregiver about the family situation at this time (0:19 <0.05), which means that adaptation of caregiver in treating patients with schizophrenia is influenced by the characteristics of the family, namely community resources, self-efficacy, caregiver coping effort, self-esteem and perception of family caregiver to the conditions experienced at this time. Perception of caregiver about the condition of today's families is affected by stress, which appears on a caregiver stress due to stressor for caring for people with schizophrenia, especially the aggressive behavior of schizophrenics.Discussion: Adaptation of caregiver was highly influential in the care of people with schizophrenia because in this case becomes one of the important points to be able to sustain the process of treatment and prevent relapse of schizophrenics.